Nutrient-coated urea mitigates deleterious impacts of salinity and supports wheat performance by enhancing antioxidant activities, photosynthetic performance and nitrogen use efficiency - Chattha, Muhammad Umer; Fatima, Fiza; Khan, Imran; Daji, Li; Chattha, Muhammad Bilal; Rasheed, Adnan; Elnour, Rehab O.; Asseri, Tahani A.Y.; Hashem, Mohamed; Alhaithloul, Haifa A.S.; Hassan, Muhammad Umair; Qari, Sameer H. (Italian Journal of Agronomy, 2024)
Soil salinization has increased over recent years and is negatively affecting crop productivity. Nutrient application is an effective strategy to improve abiotic stress tolerance in crops. The application of coated fertilizers has emerged as an excellent approach to mitigate the adverse impacts of soil salinity. Therefore, the present study was conducted to determine the effects of zinc and sulfur coated urea on the performance of wheat growing under saline conditions. The study comprised of diverse salinity stress levels; 0, 6 and 12 dS m-1, cross combined with normal urea (NU), zinc coated urea (ZCU) and sulfur coated urea (SCU). Salinity stress reduced wheat yield by impairing leaf water status, reducing photosynthetic pigments, osmolytes accumulation, potassium (K) and nitrogen (N) uptake while increasing sodium (Na) and chloride (Cl) uptake and hydrogen peroxide (H2O2), malondialdehyde (MDA) and electrolyte leakage (EL) accumulation. The application of ZCU increased the wheat yield by enhancing photosynthetic pigments, leaf water status, antioxidant activities, osmolytes accumulation, and reducing H2O2, MDA and EL accumulation. Furthermore, the significant increase in growth and yield of wheat with ZCU and SCU was also linked with improved K and N uptake, higher nitrogen use efficiency (NUE) and reduced Na and Cl concentration. Thus, the application of ZCU could be an effective approach to improve wheat productivity under saline conditions.